Validitas dan Reliabilitas Emotion Regulation Questionnaire (ERQ) Versi Bahasa Indonesia - Desi Dwi Korani; Muhammad Hudzaifah; Abdul Kholiq Ismail; Rubiyanti; Alimatus Sahrah (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study aimed to adapt and evaluate the Indonesian version of the Emotion Regulation Questionnaire (ERQ). The adaptation process involved a double-translation procedure, expert review, readability testing, and content validity analysis using Aiken’s V, which resulted in ten final items. Psychometric evaluation was conducted through Exploratory Factor Analysis (EFA) and Confirmatory Factor Analysis (CFA) using samples from Indonesia. The EFA results indicated a clear two-factor structure, with item loadings ranging from 0.45 to 0.90. The CFA confirmed the two-factor model, demonstrating good model fit indices (CFI = 0.96, TLI = 0.946, RMSEA = 0.063, SRMR = 0.049). Internal consistency was considered adequate, with Cronbach’s alpha and McDonald’s omega values of 0.83 for reappraisal and 0.77 and 0.78 for suppression, respectively. All items showed corrected item–total correlations above 0.30, indicating good item discrimination. These findings suggest that the Indonesian version of the ERQ exhibits a stable factor structure, strong construct validity, and satisfactory reliability as a measure of emotion regulation strategies. Further research is required to examine measurement invariance, temporal stability, as well as convergent and predictive validity across diverse population groups.